2021
DOI: 10.14348/molcells.2021.0101
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Suppress Severe Asthma by Directly Regulating Th2 Cells and Type 2 Innate Lymphoid Cells

Abstract: Patients with severe asthma have unmet clinical needs for effective and safe therapies. One possibility may be mesenchymal stem cell (MSC) therapy, which can improve asthma in murine models. However, it remains unclear how MSCs exert their beneficial effects in asthma. Here, we examined the effect of human umbilical cord blood-derived MSCs (hUC-MSC) on two mouse models of severe asthma, namely, Alternaria alternata-induced and house dust mite (HDM)/diesel exhaust particle (DEP)-induced asthma. hUC-MSC treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Pediatric severe asthma with fungal sensitization resulted in an increase in the number of IL-33-mediated ILC2s, Th2 cells, and steroid-resistant AHR [ 107 ]. Recently, it has been found that human umbilical cord blood-derived mesenchymal stem cells can also reduce lung type 2 (Th2 and ILC2s) inflammation [ 108 ]. Glucocorticoid is an effective drug for the treatment of asthma [ 109 ].…”
Section: Crosstalk Between Ilc2s and Cd4 + T Cells...mentioning
confidence: 99%
“…Pediatric severe asthma with fungal sensitization resulted in an increase in the number of IL-33-mediated ILC2s, Th2 cells, and steroid-resistant AHR [ 107 ]. Recently, it has been found that human umbilical cord blood-derived mesenchymal stem cells can also reduce lung type 2 (Th2 and ILC2s) inflammation [ 108 ]. Glucocorticoid is an effective drug for the treatment of asthma [ 109 ].…”
Section: Crosstalk Between Ilc2s and Cd4 + T Cells...mentioning
confidence: 99%
“…MSCs also have the potential to transdifferentiate into ectodermal lineages (neurons and keratinocytes) ( Dos Santos et al, 2019 ; Poudineh et al, 2018 ) and endodermal lineages (hepatocytes and cardiomyocytes) ( Aurich et al, 2009 ; Sgodda et al, 2007 ; Szaraz et al, 2017 ). In addition to their differentiation potential into multiple lineages, MSCs have been considered as a cell-based drug to treat various neurological disorders, such as amyotrophic lateral sclerosis ( Mazzini et al, 2003 ; Suzuki et al, 2008 ), Parkinson’s disease ( Kan et al, 2007 ; Wang et al, 2010 ), Alzheimer’s disease ( Ma et al, 2013 ; Yang et al, 2013 ), stroke ( Lee et al, 2015 ; Xin et al, 2013 ), and non-neurological diseases, such as graft versus host diseases ( Le Blanc et al, 2004 ), myocardial infraction ( Huang et al, 2019 ), type 1 diabetes ( Unsal et al, 2015 ) and severe asthma ( Shin et al, 2021 ). More than 1,300 clinical trials are ongoing or have been completed worldwide using MSCs ( https://www.clinicaltrials.gov , with a query of “mesenchymal stem cells” 2021), indicating the broad application and usefulness of naive MSCs in cell-based drug development.…”
Section: Introductionmentioning
confidence: 99%
“…ILC2s have been suggested as the innate counterpart of Th2 cells which play important roles in the development of asthma. The suppression of ILC2s by intravenous treatment with ucMSCs was also confirmed by using two different mouse models of severe asthma using Alternaria alternata and house dust mite/diesel exhaust particle 29 . Previous studies have reported that Treg upregluation may be the mechanism behind the inhibitory effects of intravenously administered ucMSCs on the Th2 response 22 .…”
Section: Discussionmentioning
confidence: 66%